Ratio to Return On Assets in Banking Subsector Companies Listed on the Indonesia Stock Exchange in 2016-2019 - Jauhari, Hendra; Devananta, Kenfi; Lais, Owen August; Gabriella, Gabriella; Januardin, Januardin (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of Cash Ratio, Capital Adequacy Ratio and Loan to Deposit Ratio on Return On Assets in banking sub-sector companies listed on the Indonesian stock exchange in 2016-2019. This research uses quantitative research methods to find the relationship between numerical data or numbers. . The data analysis model used during this research process is the multiple linear regression analysis model using the SPSS application ((Statistical Product and Service Solutions) version 24. During the 4-year period, namely; 2016-2019, there were 18 companies that met the criteria in the study. and produced 72 data samples.The results obtained are (1) It is known that the t-count Cash Ratio: 5.956 > t-table 1.996, so it can be concluded that there is an effect of X1 (Cash Ratio) on Y (ROA) (2) The t-value is known. Calculate Cash Adequacy Ratio: 3.300 > t table 1.996, so it can be concluded that there is an effect of X2 (Cash Adequacy Ratio) on Y (ROA). that there is no effect of X3 (Loan to Deposit Ratio) on Y (ROA) (4) Cash Ratio, Cash Adequacy Ratio, Loan to Deposit Ratio have a simultaneous effect on Return On Assets in Peru Banking sub-sector companies listed on the IDX for the 2016-2019 period. This is evidenced by the significance value of 0.00 indicating a value that is smaller than the predetermined significance value of 0.05.